2020
DOI: 10.3892/ijmm.2020.4684
|View full text |Cite|
|
Sign up to set email alerts
|

TUSC8 inhibits the development of osteosarcoma by sponging miR‑197‑3p and targeting EHD2

Abstract: Osteosarcoma (OS) is one of the most common malignant bone tumours and generally occurs in children and adolescents. Increasing evidence has demonstrated that dysregulated long non-coding RNAs (lncRNAs) play crucial roles in the progression of various human neoplasms. Among these, tumour suppressor candidate 8 (TUSc8) is a novel lncRNA and has been reported to function as a tumour suppressor in cervical cancer. However, the exact role of TUSc8 in OS remains largely unknown. In the present study, it was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…In the present study, we also used western blot analysis to identify EMT markers, and the results showed that EHD2 increased E-cadherin expression, whereas it reduced the expressions of N-cadherin and vimentin. Previous studies have indicated that EHD2 knockdown promotes EMT, while EHD2 overexpression inhibits EMT in osteosarcoma and liver cancer (13,27). Several studies have demonstrated that EMT promotes early epithelial cancer cell diffusion and is an essential parameter in epithelial cancer invasion and metastasis (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also used western blot analysis to identify EMT markers, and the results showed that EHD2 increased E-cadherin expression, whereas it reduced the expressions of N-cadherin and vimentin. Previous studies have indicated that EHD2 knockdown promotes EMT, while EHD2 overexpression inhibits EMT in osteosarcoma and liver cancer (13,27). Several studies have demonstrated that EMT promotes early epithelial cancer cell diffusion and is an essential parameter in epithelial cancer invasion and metastasis (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…TUSC8 and LINC01010 are reported to act as a suppressor in the invasion of multiple cancer cells in different pathways. [50][51][52][53] Multiple signatures that predict tumor prognosis also involve LINC01010. [53][54][55] AL161431.1 facilitates tumor cell proliferation and migration in endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs generally exert their regulatory role by selectively targeting protein-coding genes. Similarly, miR-197-3p has been shown to target multiple genes in human cells, such as KLF10 ( You et al,2021 ), ABCA7( Xie et al,2020 ) and EHD2 ( Fan et al,2020 ). However, TYMS as a target of miR-197-3p in any type of cancer cell has not been studied.…”
Section: Discussionmentioning
confidence: 99%